A Simple Method to Develop a Formula for Estimating Concentration Time of Drainage Design - Alfiansyah Yulianur; Sugianto Sugianto; Frystia Mala Puspita (Graduate Program of Syiah Kuala University, 2019)
Concentration time of rainfall is an important aspect to determine drainage design. A general rational formula is used to determine design flood or peak flow in urban drainage planning, especially for storm sewer design. The use of this balanced formula requires rainfall intensity, whose duration of rain is equal or more than the time of concentration. This time of concentration is determined using an estimation formula whose formation requires measurement data of the time of concentration. This study introduces how to measure the time of concentration using the concept of-rational-hydrograph, in which peak flow occurs at the time of concentration. To fulfill the aim of this research, an experimental of catchment area planted with Zoysia Japonica grass and showered with a rainfall simulator was conducted. The length of the flow path on the land, L, given in 5 variations, namely 50 cm, 100 cm, 150 cm, 200 cm, and 250 cm, was used. The slope of the land, S, is given in 3 variations, namely 2.8 %, 5,6%, and 8.8%. For each variation of L and S, the experimental catchment area was poured with a fixed rainfall intensity, which is 60 mm/hour. The flow was measured every 5 minutes intervals. Then, from the relationship of flow and time, a rational hydrograph was formed, from which the time of concentration, Tc, was deduced. This Tc value was treated as the measured Tc to form the Tc estimation formula using the regression formula. The formula is Tc = 3.543 + 1.211 L – 17.119 S, with the coefficient of determination R2 = 0.98. These results show that the determination of Tc using the concept of the rational- hydrograph is acceptable. This formula applies to L and S values greater than zero and applies to land covered by Zoysia Japonica grass. Further research is needed for other types of land cover to validate the formula obtained in this research.